2011
DOI: 10.1002/adsc.201100522
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric CS Bond Formation: Synthesis of α‐Methylene‐β‐mercapto Esters with Simple Alkyl Thiols

Abstract: A highly efficient organocatalytic enantioselective C À S bond formation reaction between simple alkyl thiols and Morita-Baylis-Hillman (MBH) carbonates is described. The optically active a-methylene b-mercapto esters could be obtained under mild reaction conditions with excellent enantioselectivities (up to 97% ee). The broad scope and simple operation make this methodology very practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Some complementary experimentsw ere carriedo ut in the case of cyclohexyl thiol. As reportedb yZ hu and Cheng, [7] using MgSO 4 ,a sa na dditive, in 1,4-dioxanec ould accelerate the reaction rate of the allylic substitution with thiols. On the contrary,inour studies, enantiomeric excess decreased dramatically,w ithoute ffect on reactivity,w hen adding 20 mol %o f MgSO 4 was employed (Table 4, entries 18-20).…”
mentioning
confidence: 57%
See 3 more Smart Citations
“…Some complementary experimentsw ere carriedo ut in the case of cyclohexyl thiol. As reportedb yZ hu and Cheng, [7] using MgSO 4 ,a sa na dditive, in 1,4-dioxanec ould accelerate the reaction rate of the allylic substitution with thiols. On the contrary,inour studies, enantiomeric excess decreased dramatically,w ithoute ffect on reactivity,w hen adding 20 mol %o f MgSO 4 was employed (Table 4, entries 18-20).…”
mentioning
confidence: 57%
“…[7] It should be noted that all catalytic systems used fort he CÀSb ond formations tartedf rom modified MBH adducts are tertiarya mine-basedo rganocatalysts. [5][6][7] No example of ap hosphine-catalyzed allylic substitution of MBH acetate or carbonate adducts for CÀSbond formation has been reported so far.In continuation of our research on the design and synthesis of new chiral organocatalysts, we have recently reported the synthesis of new bifunctional chiral phosphine-thiourea organocatalysts A, B and C,d erived from l-proline ( Figure 1). We have also described their applications in the asymmetric[ 3 + +2] cyclization between ethyl-butan-2,3-dienoate and N-benzylidene-p-toluenesulfonamide.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lewis base-catalyzed asymmetric allylic alkylations (AAA) of Morita–Baylis–Hillman (MBH) adducts [56], such as acetates and carbonates, have become an attractive option to access various chiral C - [719], N - [2025], O - [2630], P - [3133] and S -allylic [34] and spirocyclic compounds [3537]. Several protocols have been established to introduce fluorine atoms in AAA of MBH adducts.…”
Section: Introductionmentioning
confidence: 99%